2015
DOI: 10.3389/fnbeh.2015.00042
|View full text |Cite
|
Sign up to set email alerts
|

Social behavioral changes in MPTP-treated monkey model of Parkinson's disease

Abstract: Parkinsonian patients experience not only the physical discomfort of motor disorders but also the considerable psychological distress caused by cognitive deficits and behavioral disorders. These two factors can result in a disruption of social relationships during the symptomatic and even the presymptomatic motor states of the disease. However, it remains difficult, if not impossible, to evaluate social relationships in presymptomatic patients. The present study focused on the evaluation of social relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…While males receiving a partial MPTP dose were somewhat impacted by motor deficit, males receiving the full MPTP dose were more prone to exhaustion-like behavior following the intrusion. These results are similar to those of Durand et al [33], who reported changes in social relationships in female rhesus monkeys ( Macaca mulatta ) treated with MPTP (with both low and high dose regimens). Such changes occurred before motor or cognitive impairments were detected and were most common in subordinate animals.…”
Section: Discussionsupporting
confidence: 91%
“…While males receiving a partial MPTP dose were somewhat impacted by motor deficit, males receiving the full MPTP dose were more prone to exhaustion-like behavior following the intrusion. These results are similar to those of Durand et al [33], who reported changes in social relationships in female rhesus monkeys ( Macaca mulatta ) treated with MPTP (with both low and high dose regimens). Such changes occurred before motor or cognitive impairments were detected and were most common in subordinate animals.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, MPTP lesions in monkey can lead to a decrease in behavioral activity 117 and goal-directed behaviors, 118 , 119 and to social behavioral changes. 120 However, because of the lack of neuroanatomical selectivity of systemic MPTP administration, and despite in-depth multi-correlational and neuroimaging analyses, it has yet to be determined from these studies whether these behavioral impairments result from a loss of dorso- or ventro-striatal function.…”
Section: Discussionmentioning
confidence: 99%
“…The faster peripheral metabolism in small rodents may render the use of some tracers problematic and has led to misrepresentation of their utility: an example of a tracer where this has been an issue is 18 F-DOPA which is under-used in rodents but extensively used in large animal models [13,16,17,21]. Recent studies using inhibitors to slow or reduce its peripheral metabolism have shown that both 18 F-DOPA uptake and dopamine turnover can be measured in rodents despite the faster tracer metabolism [74].…”
Section: Caveats In Imaging Animal Modelsmentioning
confidence: 99%